2015
DOI: 10.1149/2.0251505jes
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Redox Phenomena for Enhanced Aqueous Supercapacitors

Abstract: The paper reports on electrochemical characterization of several supercapacitors operating in aqueous electrolytes and discusses a strategy for enhancing their performance. Various electrolytes such as alkaline (6 mol L −1 KOH), acidic (1 mol L −1 H 2 SO 4 ) and neutral (1 mol L −1 KI and 1 mol L −1 Na 2 S 2 O 3 ) were investigated in terms of electrochemical stability and redox activity. A new concept of capacitor with two electrodes operating in different electrolytes is demonstrated. The positive electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 39 publications
3
51
1
Order By: Relevance
“…According to Ref. [16], the low η E ≈ 50% at 1.6 V for the KI system could be due to a blockage of the hydrogen adsorption sites by the iodide reaction products (iodine and iodates), leading to irreversible di-hydrogen evolution. Misleading coulombic efficiency values up to 100%, without evaluation of energy efficiency, have also been reported for other faradaic systems (conducting polymer, functionalized carbon with redox electrolyte, etc.)…”
Section: Performance Overestimation Of Capacitors Based On Redox Processmentioning
confidence: 96%
“…According to Ref. [16], the low η E ≈ 50% at 1.6 V for the KI system could be due to a blockage of the hydrogen adsorption sites by the iodide reaction products (iodine and iodates), leading to irreversible di-hydrogen evolution. Misleading coulombic efficiency values up to 100%, without evaluation of energy efficiency, have also been reported for other faradaic systems (conducting polymer, functionalized carbon with redox electrolyte, etc.)…”
Section: Performance Overestimation Of Capacitors Based On Redox Processmentioning
confidence: 96%
“…The voltage limit for cells in aqueous electrolytes is the positive electrode, due to oxidation of the carbon electrode material and/or corrosion of current collectors when the thermodynamic potential of water oxidation is exceeded ,. To solve such issue, Frąckowiak et al suggested an asymmetric cell with KOH and H 2 SO 4 (or LiNO 3 ) electrolytic media for the negative and positive electrodes, respectively, both separated by two porous glassy fiber membranes ,. Unfortunately, a sharp capacitance decrease of the (−) KOH/LiNO 3 (+) system occurred in the first 500 cycles, which suggests possible mixing of electrolytes due to the use of a porous separator …”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been devoted to the redox‐mediator‐enhanced supercapacitors. As a result, a variety of redox mediators and electrolyte systems have been developed …”
Section: Progresses In Redox‐mediator‐enhanced Supercapacitorsmentioning
confidence: 99%
“…Therefore, the CV curve of the positive electrode now shows a pair of redox peaks and the negative one a rectangular shape (Figure g) and the GCD curve of the positive electrode exhibits the sloping potential plateaus whereas the potential of the negative electrode varies linearly with time (Figure h). After the first successful attempt of enhancing the capacitance by introducing Ag + as mediator, a large number of redox mediators were developed for supercapacitors . Based on the used redox mediators, the single‐redox‐mediator‐enhanced supercapacitors can be divided into three categories: metal‐mediator‐based supercapacitors, inorganic‐mediator‐based supercapacitors, and organic‐mediator‐based supercapacitors.…”
Section: Progresses In Redox‐mediator‐enhanced Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation